2022
DOI: 10.17759/pse.2022270201
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Basic Human Values and Use of Information and Communication Technology among Younger and Older Generations

Abstract: This article presents the results of a study on the interrelationship between values and the use of Information and Communication Technology (ICT) among younger and older Russians. It was assumed that for these age groups basic values play a different role in encouraging or discouraging the use of ICT. The study was carried out using a socio-psychological survey. The questionnaire included the authors’ methodology for measuring involvement in the use of ICT and a short version of Sh. Schwartz’s questionnaire f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
4
0
0
Order By: Relevance
“…In the context of the research devoted to involvement in ICT, the relationship between higher-order values and involvement in online learning was an expected outcome, which corresponded with the results of existing research on the relevant topic (Bagchi et al, 2015;Tatarko et al, 2022). Online learning is an environment where modern technologies are essential for its effective functioning.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the context of the research devoted to involvement in ICT, the relationship between higher-order values and involvement in online learning was an expected outcome, which corresponded with the results of existing research on the relevant topic (Bagchi et al, 2015;Tatarko et al, 2022). Online learning is an environment where modern technologies are essential for its effective functioning.…”
Section: Discussionsupporting
confidence: 74%
“…Bagchi and her colleagues (Bagchi et al, 2015) found that in developed countries, the values of Сonformity, Tradition, Security and Power contribute to involvement in the use of ICT, and in developing countries -Achievement, Stimulation, Self-Direction, Tradition, and Security. The obtained results partially confirm the study of Tatarko and his colleagues (Tatarko et al, 2022) -the exception is the lack of connection with the value of Stimulation. Since there is a positive correlation between the individual's values and her involvement in ICTs, we consider that online learning, as one of the mediums of implementation and application of ICTs, will also be conditioned by the individual's values.…”
Section: Introductionsupporting
confidence: 87%
“…In the context of the research devoted to involvement in ICT, the relationship between higher-order values and involvement in online learning was an expected outcome, which corresponded with the results of existing research on the relevant topic (Bagchi et al, 2015;Tatarko et al, 2022). Online learning is an environment where modern technologies are essential for its effective functioning.…”
Section: Discussionsupporting
confidence: 74%
“…Bagchi and her colleagues (Bagchi et al, 2015) found that in developed countries, the values of Сonformity, Tradition, Security and Power contribute to involvement in the use of ICT, and in developing countries -Achievement, Stimulation, Self-Direction, Tradition, and Security. The obtained results partially confirm the study of Tatarko and his colleagues (Tatarko et al, 2022) -the exception is the lack of connection with the value of Stimulation. Since there is a positive correlation between the individual's values and her involvement in ICTs, we consider that online learning, as one of the mediums of implementation and application of ICTs, will also be conditioned by the individual's values.…”
Section: Introductionsupporting
confidence: 87%